China's special economic zones in Africa: context, motivations and progress - António, N. S.; Ma, S. (Euro Asia Journal of Management, 2015)
As more and more countries set foot in Africa, there is a growing attention on China’s role and engagement in the region. The approaches are very diverse and if some are more skeptical, others praise factors that particularly shape China’s current move to Africa such as a focus on development cooperation and on establishing strategic partnerships. These would also add that China has had a very positive and influential role in Africa through aiding many countries to solve imminent problems and to assist with knowledge transfer. In this paper, we first discuss the context of the launching of Special Economic Zones in Africa by examining the historic development of the Sino-Africa relationship, and analyze China’s motivations for establishing the Special Economic Zones in the continent. Finally, we present the latest progress of the Special Economic Zones’ development and discuss how they contribute toward the presence of China in Africa.